(untitled) (CIPEEX, 2024)
BREAST CANCER IS THE MOST COMMON CANCER IN WOMEN IN BRAZIL AND ONE OF THE LEADING CAUSES OF DEATH FROM CANCER IN THE WORLD, WHERE MASTECTOMY IS THE MAIN FORM OF TREATMENT,THIS CAUSES DYSFUNCTIONS IN A WOMAN’S PHYSIOLOGY, HARMING HER QUALITY OF LIFE. THE AIM OF THE STUDY WAS TO ANALYZE THE MAIN DAMAGE CAUSED BY THE PROCEDURE AND TO FIND THE BEST EVIDENCE OF EXERCISES AND PROCEDURES PERFORMED BY PHYSIOTHERAPISTS IN ORDER TO IMPROVE QUALITY OF LIFE. THIS IS A NARRATIVE REVIEW WITH THE GUIDING QUESTION: WHAT ARE THE MAIN SEQUELAE AFTER MASTECTOMY AND WHAT ARE THE BEST INTERVENTIONS FOR THEM? ELEVEN ARTICLES WERE SELECTED TO COMPOSE THE WORK, AS THEY HELPED ANSWER THE GUIDING QUESTION AND HAD A PUBLICATION DATE BETWEEN 2019 AND 2023. THE MOST WIDESPREAD SEQUELAE IN THE ARTICLES WERE DECREASED RANGE OF MOTION, PAIN AND EDEMA AND DIFFICULTY ADAPTING TO DAILY ROUTINE. THE MAIN INTERVENTION FOUND WAS KINESIOTHERAPY TO REDUCE DAMAGE, FOLLOWED BY COMPRESSIVE THERAPY AND LYMPHATIC DRAINAGE. THEREFORE, IT CAN BE CONCLUDED THAT PHYSIOTHERAPY HAS A WIDE RANGE OF TREATMENTS WHEN IT COMES TO MASTECTOMIZED PATIENTS, BUT FURTHER STUDIES ARE NEEDED TO DETERMINE THE EFFECTIVENESS OF EACH ONE.